2013
DOI: 10.1111/sjop.12056
|View full text |Cite
|
Sign up to set email alerts
|

Social problem‐solving, perceived stress, depression and life‐satisfaction in patients suffering from tension type and migraine headaches

Abstract: This study aimed at investigating social problem solving, perceived stress, depression, and life-satisfaction in patients with tension type and migraine headaches. Forty-nine migraine and 42 tension type headache patients (n = 91) consenting to participate were compared to a total of 49 matched healthy control group. Participants filled in a questionnaire consisting self-report measures of problem solving, perceived stress, depression and life satisfaction. They were also asked about headache duration, frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 37 publications
3
32
1
2
Order By: Relevance
“…It has been found that migraine patients have higher levels of perceived stress than healthy controls [6, 7]. In addition, identified stress levels are higher in migrainous women than those in migrainous men [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that migraine patients have higher levels of perceived stress than healthy controls [6, 7]. In addition, identified stress levels are higher in migrainous women than those in migrainous men [6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic headaches often have high levels of psychological distress [8], including depressive symptoms [23; 37], anxiety [25; 41; 54], and somatization [21; 48]. Psychological distress can exacerbate the adverse impact of headache on health-related quality of life (HRQOL) [22], and may reduce efficacy of headache interventions [22].…”
Section: Introductionmentioning
confidence: 99%
“…In a study in USA, showed that those who reported <16 years of education had a significantly higher mean BMI (Body Mass Index), were more likely to be obese, were more likely to experience depression, and have a higher mean BID (Body Image Dissatisfaction) score compared to those with ≥16 years of education [41]. Another study suggested cognitive behavioral problem solving therapy or training might be a viable option for reducing levels of stress and depression, and to increase lifesatisfaction in patients suffering from primary headache [42].…”
Section: Discussionmentioning
confidence: 99%